Improving Upper Extremity Function and Quality of Life with a Tongue Driven Exoskeleton: A Pilot Study Quantifying Stroke Rehabilitation. (18th December 2017) - Housley, Stephen N.; Wu, David; Richards, Kimberly; Belagaje, Samir; Ghovanloo, Maysam; Butler, Andrew J.
Abstract : Stroke is a leading cause of long-term disability around the world. Many survivors experience upper extremity (UE) impairment with few rehabilitation opportunities, secondary to a lack of voluntary muscle control. We developed a novel rehabilitation paradigm (TDS-HM) that uses a Tongue Drive System (TDS) to control a UE robotic device (Hand Mentor: HM) while engaging with an interactive user interface. In this study, six stroke survivors with moderate to severe UE impairment completed 15 two-hour sessions of TDS-HM training over five weeks. Participants were instructed to move their paretic arm, with synchronized tongue commands to track a target waveform while using visual feedback to make accurate movements. Following TDS-HM training, significant improvements in tracking performance translated into improvements in the UE portion of the Fugl-Meyer Motor Assessment, range of motion, and all subscores for the Stroke Impact Scale. Regression modeling found daily training time to be a significant predictor of decreases in tracking error, indicating the presence of a potential dose-response relationship. The results of this pilot study indicate that the TDS-HM system can elicit significant improvements in moderate to severely impaired stroke survivors. This pilot study gives preliminary insight into the volume of treatment time required to improve outcomes.